Guardians of Horsa. [4], The fire oath - Black, Roan (Black, Roan. Guardians of Horsa, 2024)
The Guardians seek a hidden relic inside the Fire Realm and soon learn of the Fire Oath, a promise Gamma Ray made as prince of the Solar Herd to protect his realm at all costs.